1999
DOI: 10.1200/jco.1999.17.9.2781
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HER2/erbB-2 Correlates With Survival in Osteosarcoma

Abstract: The correlation of HER2/erbB-2 expression with histologic response to preoperative chemotherapy and event-free survival in this study suggests that HER2/erbB-2 should be evaluated prospectively as a prognostic indicator. The correlation also suggests that clinical trials of antibodies that target this receptor, such as recombinant humanized anti-HER2 monoclonal antibody (Herceptin; Genentech, San Francisco, CA), should be considered for the treatment of osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
182
3
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(199 citation statements)
references
References 27 publications
9
182
3
5
Order By: Relevance
“…Some immunohistochemical studies demonstrated a significant correlation between Her-2/neu expression and a poor histologic response to preoperative chemotherapy, a decreased event-free survival as well as an increased risk of pulmonary metastases. [17][18][19]23 In contrast, other studies observed Her-2/neu expression irrespective of histologic subtype and grade that was not associated with response to preoperative chemotherapy and clinical outcome. 22 Further reports did not observe Her-2/neu overexpression or even reported complete absence of Her-2/neu Figure 5 RNA was extracted from the indicated numbers of lasermicrodissected cells obtained from a decalcified, paraffinembedded and formalin-fixed osteosarcoma section and converted to cDNA.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Some immunohistochemical studies demonstrated a significant correlation between Her-2/neu expression and a poor histologic response to preoperative chemotherapy, a decreased event-free survival as well as an increased risk of pulmonary metastases. [17][18][19]23 In contrast, other studies observed Her-2/neu expression irrespective of histologic subtype and grade that was not associated with response to preoperative chemotherapy and clinical outcome. 22 Further reports did not observe Her-2/neu overexpression or even reported complete absence of Her-2/neu Figure 5 RNA was extracted from the indicated numbers of lasermicrodissected cells obtained from a decalcified, paraffinembedded and formalin-fixed osteosarcoma section and converted to cDNA.…”
Section: Discussionmentioning
confidence: 78%
“…Using immunohistochemical assays, some studies demonstrated Her-2/neu overexpression in osteosarcoma tissues, which strongly correlated with early pulmonary metastases, less tumor necrosis after preoperative chemotherapy and a significantly decreased event-free survival rate. [17][18][19] Other studies did not observe any Her-2/neu expression or only cytoplasmic expression 20 which is in contrast to membranous positivity considered as non-specific. In these studies, observation of cytoplasmic positivity was independent of histologic subtype and grade and not associated with response to preoperative chemotherapy or disease progression.…”
mentioning
confidence: 86%
“…Axial lesions have an inferior outcome [35,36] and the presence of clinically detectable primary metastatic disease correlates with poor prognosis [35,37]. Protein expression in serum, such as levels of LDH or alkaline phosphatase correlate with outcome [1,38] and other molecular markers are also being investigated to determine the relative significance for predicting prognosis [39,40]. Considering that the major purpose of cancer biology research is to identify prognostic factors and therapeutic targets, obtaining a better knowledge of molecular pathology in osteosarcoma is continuously needed.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The human epidermal growth factor receptor (HER2) is expressed by up to 60% of primary OS and correlates with poor prognosis. 10,11 Previously, we have shown that genetically modified T cells expressing a HER2-specific chimeric antigen receptor exerted potent antitumor activity against OS cells in vitro. Furthermore, HER2-specific T cells induced regression of established OS xenografts in mice, increasing survival in treated animals.…”
Section: Introductionmentioning
confidence: 99%